Impact of hypercoagulable state on Crohn’s disease severity and progression: transcriptomic and single-cell analyses of the ileum - Wu, Fengfei; Wu, Fangting; Yang, Hui; Xie, Wenting; Zhang, Sinan; Zhou, Lihua; Xie, Fang; Bai, Lan; Huang, Miaoxing; Liu, Side (Frontiers in Immunology, 2025)
BackgroundThe mechanisms linking hypercoagulability to disease severity in Crohn’s disease (CD) remain poorly understood. Through integrated transcriptomic and single-cell analyses of ileal tissues, we identified a novel CCR6+OLFM4+ intestinal stem cell subpopulation that bridges coagulation and inflammation in CD.MethodsA cohort of 78 CD patients was established, utilizing transcriptomic data from three independent ileal samples obtained from the GEO database as discovery and validation datasets. Coagulation-related DEGs (CRGs) were determined via AmiGO 2 and KEGG databases. Based on these CRGs, CD patients were subclustered, coagulation scores were calculated, and gene expression changes were evaluated. Public single-cell RNA sequencing data from CD patient ileal epithelial cells were analyzed to identify key target cells influenced by coagulation. Immune infiltration was evaluated based on coagulation scores across subgroups. Ileal tissues from CD patients with different coagulation statuses were examined using Immunofluorescence Staining.ResultsSingle-cell analysis of ileal epithelium revealed a novel CCR6+OLFM4+ stem cell subpopulation that was significantly expanded in CD patients with hypercoagulability (P<0.05). These cells showed marked upregulation of PI3K-Akt signaling and correlated strongly with disease severity. Immunofluorescence validation confirmed a 2.3-fold increase in CCR6+OLFM4+ cells in the epithelial layer of hypercoagulable CD patients compared to normocoagulable controls. The concurrent activation of coagulation pathways and immune cell infiltration in CD ileum suggests this stem cell subpopulation may serve as a critical link between hypercoagulability and disease progression.ConclusionOur findings nominate CCR6+OLFM4+ stem cells as cellular mediators of coagulation-associated CD progression, suggesting the CCR6-PI3K-Akt axis as a potential therapeutic target requiring validation in larger cohorts.